An analysis on cash flow statement of Pelorus Intelligence & Technology Academy Sdn Bhd for year 2004 to 2008 / Nazirah Nasir - Nasir, Nazirah (Faculty of Business and Management, 2010)
This paper studies on the Analysis of Cash Flow Statement for Pelorus Intelligence & Technology Academy Sdn. Bhd. This study will focus on the company annually cash flow from 2004 to June 2008. A rough idea on the cash position of a company can be obtain by looking at its company cash flow statement. However, there is a need for reliable information in which every party can use for better decision making and to enhance the understanding over an organization’s actual business performance, and not just based on assumptions or an idea over a particular situation. For this reason, researcher will conduct a thorough cash flow analysis to analyze the cash flow statement that meet the organization’s goals, to identify the limitation in gained and to identify the strategy implemented by the company whether the company achieve the policies been made.